Modicella albostipitata, a new species of sporocarp-forming fungus from New Zealand (Mortierellaceae: Mortierellomycota) - Cooper, Jerry A.; Park, Duckchul (Phytotaxa, 2020)
Modicella is an unusual genus within the Mortierellaceae because it forms relatively large terrestrial sporocarps. The two existing described species are rarely encountered. We describe a new species, M. albostipitata, from New Zealand in the southern hemisphere, which is both morphologically and phylogenetically distinct from the described species.